Effects On The Quality Of Accounting Data Of Business Entities Factors - Rakhmatova Shakhnoza Shukurovna; Khotamov K.R. (Genius Publishing Group, 2022)
This article discusses the factors that affect the quality of accounting data of business entities
Keywords: Economics; market relations; contractor